Comparative biochemical characterization of mammalian-derived CYP11A1s with cholesterol side-chain cleavage activities. Issue 229 (May 2023) - Liu, Ruxin; Pan, Yunjun; Wang, Ning; Tang, Dandan; Urlacher, Vlada B.; Li, Shengying
Abstract: Steroid drugs, the second largest class of pharmaceuticals after antibiotics, have shown significant anti-inflammatory, anti-allergic, and endocrine-regulating effects. A group of cytochrome P450 enzymes, namely, CYP11A1 isoenzymes from different organisms are capable of converting cholesterol into pregnenolone, which is a pivotal reaction in both steroid metabolism and (bio)synthetic network of steroid products. However, the low activity of CYP11A1s greatly restricts the industrial application of these cholesterol side-chain cleavage enzymes. Herein, we investigate ten CYP11A1 enzymes of different origins and in vitro characterize two CYP11A1s with a relatively higher expression level from Capra hircus and Sus scrofa, together with the CYP11A1s from Homo sapiens and Bos taurus as references. Towards five selected sterol substrates with different side chain structures, S. scrofa CYP11A1 displays relatively higher activities. Through redox partners combination screening, we reveal the optimal redox partner pair of S. scrofa adrenodoxin and C. hircus adrenodoxin reductase. Moreover, the semi-rational mutagenesis for the active sites and substrate entrance channels of human and bovine CYP11A1s is performed based on comparative analysis of their crystal structures. The mutant m Bt CYP11A1-Q377A derived from mature B. taurus CYP11A1 shows a 1.46 times higher activity than the wild type enzyme. These results not only demonstrate the tunability of the highly conserved CYP11A1 isoenzymes, but also lay a foundation for the following engineering efforts on these industrially relevant P450 enzymes. Highlights: Two new membrane-bound CYP11A1s were biochemically characterized in vitro. SsCYP11A1 shows relatively higher activity towards five selected sterol substrates. The optimal redox partners were identified through activity screening. Alanine scanning for the active sites and substrate entrance tunnels was performed. Mutant Q377A of bovine CYP11A1 shows improved activity towards cholesterol.